Laxens uppströmsvandring i den restaurerade och flödesreglerande Umeälvens nedre del - Johansson, Joakim (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2015)
The expansion of hydroelectric power has negatively affected the Baltic stock of Atlantic salmon (Salmo salar L.). To enable spawning migration of salmon in flow controlled rivers with intact wild stocks, bypass channels and resting pools with smaller flows are constructed to help salmonids in their migration upstream. Some of these restoration actions to help migrating fish are seen in the old river bed in the lower part of river Umeälven where this study was undertaken. Previous research indicates a large loss of potential spawning salmon due to problematic migration routes and slow migration through the old river bed. These migratory problems are assumed to limit the population growth of salmon in the river. This study describes the Baltic salmon migration through the old river bed, from the confluence area to the fish ladder downstream of the dam in Norrfors, when they pass man made constructions in the river aimed to help them upstream. In the summer of 2013 (June-July ) 148 salmon (60-116 cm) was tagged with radiotransmitters at the mouth of river Umeälven, and followed on their upstream migration in the old river bed. I focussed on how an increase and change in flow regimes (by changing the spill flow) affected the salmon migration behavior on this section. The restoration of the new pool area in Baggböle rapids enabled salmon to reside in the area and not immediately return downstream due to a change in the spill flow. 99 % of all salmons from the confluence area was registered at some time in Baggböle. A higher spill flow attracted salmon into the old river bed to reach a constructed holding pool, while lower flow attracted salmon to swim past the top of Baggböle rapids. Ninety percent of the salmons that entered the study site left the confluence area or entered the Baggböle rapids in high flow. Subsequently, 70 % swam upstream from Baggböle in low flow. The passage past Kungsmo has become faster and with higher success since the restoration of this site, but spill flow, or flow changes, could not be observed to be important for the fish to pass this stretch. The overall results of the upstream migration through the old river bed from this year are better than in previous year’s studies. Eighty five percent of the salmons made it from the confluence area up to the bottom of the fish ladder in Stornorrfors. This shows that regulated spill changes together with man made constructions can highly affect salmon migration in regulated rivers positively.